IMPLEMENTATION OF THE NARRATIVE WRITING HABIT PROGRAM IN THE RESULT CHAIN-BASED HISTORY SOCIAL SCIENCES LEARNING IN GRADE V OF STATE ELEMENTARY SCHOOL 116 PALEMBANG - Ayu Astuti; Muhammad Iqbal Birsyada (SOSIOEDUKASI, 2026)
In this study, the Results Chain technique was used to describe the implementation of a narrative writing habituation program in the History Social Studies subject in fifth-grade students of SD Negeri 116 Palembang. Two cycles of planning, implementation, observation, and reflection were used in the Classroom Action Research (CAR) design. Thirty fifth-grade students and their Social Studies teachers served as subjects. Observations, narrative writing assessments, motivation surveys, and documentation were used to collect data. Qualitative and quantitative descriptive methods were then used for analysis. Based on the findings, the use of Results Chain successfully clarified the causal relationship between students' historical knowledge acquisition and writing practice activities. Between the first and second cycles, students' enthusiasm and writing participation increased from "sufficient" to "good" categories, and the average writing score increased from 73 to 85. Therefore, the use of the Results Chain-based narrative writing habituation program improved students' narrative writing skills and learning outcomes in the History Social Studies subject.